The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00277-008-0623-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 789Ala/Ala genotype on quantitative type of von Willebrand disease

Abstract: von Willebrand factor (VWF) is a complex multimeric plasma glycoprotein encoded by an approximately 178-kb large VWF gene located on the short arm of chromosome 12 (12p13.2). VWF plays an important role in hemostasis through binding with platelet GpIbalpha receptors. We made an attempt to correlate the 789Ala/Ala genotype of the VWF with VWF:Ag level in different types of unrelated von Willebrand disease (VWD) patients and healthy controls. VWF assays and other coagulation screening tests have been done for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…10 In the present study, the p.Thr789Ala variant was significantly associated with higher plasma VWF:Ag levels, and although there is some controversy regarding the direction of this effect, most previous results agree with these findings. 7,9,[35][36][37][38][39][40] The p.Thr789Ala variant is located in exon 18 of VWF, within the D' domain, which is critically involved in VWF multimerization and secretion, and in the VWF/FVIII interaction. 9,41,42 Although p.Thr789Ala was not predicted to be deleterious by any of the in silico algorithms used (►Table 2), recently, it has been described by in vitro and in vivo assays the mechanism by which this variant would modulate VWF:Ag levels in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…10 In the present study, the p.Thr789Ala variant was significantly associated with higher plasma VWF:Ag levels, and although there is some controversy regarding the direction of this effect, most previous results agree with these findings. 7,9,[35][36][37][38][39][40] The p.Thr789Ala variant is located in exon 18 of VWF, within the D' domain, which is critically involved in VWF multimerization and secretion, and in the VWF/FVIII interaction. 9,41,42 Although p.Thr789Ala was not predicted to be deleterious by any of the in silico algorithms used (►Table 2), recently, it has been described by in vitro and in vivo assays the mechanism by which this variant would modulate VWF:Ag levels in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…All eight VWD3 families were included for linkage marker including VWF1, VWF2 and Rsa I analysis by PCR as previously described . Restriction digestion other using Rsa I enzyme was done and digested product was analysed on agarose gel . PAGE followed by silver staining was performed to detect the VWF1 and VWF2 alleles.…”
Section: Genotypic Analysismentioning
confidence: 99%
“…Several studies have previously used restriction fragment length polymorphisms and variable number of tandem repeats (VNTR) within intron 40 of the von Willebrand factor (VWF) for tracking the defective alleles in VWD family [4][5][6][7][8][9]. One of these polymorphic sites in VWF exon 18 RsaI (789Thr/Ala), reported to be studied in different populations [7,10]. Studies have reported that VNTR instability is rare and occurs due to gain or loss of ATCT repeat unit [11,12].…”
mentioning
confidence: 99%
“…Platelet aggregation has been done using platelet-rich plasma (PRP) at a standard count of 300 Â 10 9 /L. 6 Mixing aggregation study of patient PRP with normal pool plasma (NPP) was also performed to confirm the diagnosis of VWD, and response was recorded with the use of aggregometer (Chrono-Log, Havertown, Pennsylvania). The factor VIII coagulant (FVIII:C) activity was assayed by manual clotting method using FVIIIdeficient plasma (Diagnostica Stago, Chausson, Asnieres, France) that has been standardized for the routine purpose in our laboratory.…”
Section: Coagulation Tests and Aggregation Studiesmentioning
confidence: 99%